Impact of hydration status on haemodynamics, effects of acute blood pressure‐lowering treatment, and prognosis after stroke. (10th October 2018) - Billington, Charlotte K.; Appleton, Jason P.; Berge, Eivind; Sprigg, Nikola; Glover, Mark; Bath, Philip M. W.
Abstract : Aims: Although high blood pressure (BP) is common in acute stroke and associated with poor outcome, the Efficacy of Nitric Oxide in Stroke (ENOS) trial showed no beneficial effect of antihypertensive treatment in this situation. Antihypertensive agents have accentuated effects in dehydrated patients. We assessed the impact of dehydration on haemodynamics, the effects of antihypertensive treatment, and prognosis in the ENOS trial. Methods: ENOS randomized 4011 patients with acute stroke and raised systolic BP to a glyceryl trinitrate (GTN) patch or no GTN patch, and to continue or to stop existing antihypertensive treatment within 48 h of onset. The primary outcome was functional outcome (modified Rankin Scale, mRS) at day 90. Blood markers of dehydration at baseline were collected at two sites ( n = 310) and their relationship with haemodynamics and outcome was assessed. Results: There were no significant associations between dehydration markers and fall in blood pressure from baseline to day 1, and no significant interaction with allocated treatment. Overall, increasing urea was associated with an unfavourable shift in mRS [odds ratio 3.43, 95% confidence interval (CI) 1.42, 8.32; P = 0.006] and increased risk of death at day 90 (hazard ratio 4.55, 95% CI 1.51, 13.66; P = 0.007). Conclusions: Blood pressure‐lowering treatment was safe in dehydrated patients, with no precipitous changes in BP, thus supporting its use in acute stroke prior to blood markers of dehydration becoming available. Increased baseline urea was associated with poor prognosis after stroke.